Promosi Kesehatan Keluarga dalam Pencegahan Obesitas pada Anak Usia 6-12 Tahun - Sety Julita; Meri Neherta; Fitra Yeni (FORIKES, 2021)
Overweight or obesity is one of the major health problems in the world, occurs in children which has become a global epidemic that must be addressed, as well as the fifth serious cause of death in the world. So that the increased risk of degenerative diseases and death, therefore it takes various kinds of efforts and prevention programs to prevent the effects of obesity. The purpose of this study was to analyze the effect of family health promotion on obesity prevention in children aged 6-12 years. The research method in the form of systematic review starts from searching data using 5 databases. Researchers used five databases, namely PubMed, ScienceDirect, DOAJ, ERIC and SAGE with a span of years from 2015-2020. Articles were searched using keywords that have been determined by the researcher and then the articles were extracted based on inclusion and exclusion criteria using the PRISMA protocol. So that 16 articles were found that match the criteria of the JBI critical appraisal tools to be analyzed. The results of the study from a review of 16 articles found that the health education that was given mostly used the lecture method while the most used media were books, posters and telephones. In conclusion, all the interventions in 16 articles can prevent obesity in children. It is recommended for further researchers to research results. This study can be used as a new person who chooses ideas or topics in subsequent research using Meta-analysis designs or original research research. Keywords: children; intervention; health promotion; prevention; obesity ABSTRAK Obesitas adalah salah satu masalah kesehatan utama di dunia pada anak-anak yang harus segera ditanggani, serta penyebab kematian kelima di dunia. Sehingga meningkatnya risiko terjadinya penyakit degeneratif dan kematian, dibutuhkan bebagai macam upaya pencegahan untuk mencegah dampak dari obesitas. Tujuan penelitian ini adalah untuk menganalisis pengaruh promosi kesehatan keluarga terhadap pencegahan obesitas pada anak usia 6-12 tahun. Metode penelitian berupa systematic review ini dimulai dari pencarian data menggunakan 5 database yaitu PubMed, ScienceDirect, DOAJ, ERIC dan SAGE dengan rentang tahun dari 2015-2020. Artikel dicari dengan menggunakan kata kunci “children, health promotion, family, prevention, obesity” yang sudah ditentukan peneliti dan kemudian artikel di ekstraksi berdasarkan kriteria inklusi dan ekslusi dengan menggunakan prokotol PRISMA. Sehingga ditemukan 16 artikel yang sesuai dengan kriteria the JBI critical appraisal tools untuk dianalisis. Hasil penelitian dari 16 artikel intervensi pendidikan kesehatan berfokus pada program peningkatan makan sehat seimbang seperti makan buah dan sayuran, diet sehat, penyediaan makan dirumah, orang tua menyusun menu makanan yang bervariasi, mengubah porsi makan setengah piring berisikan sayuran, aktivitas fisik Semua artikel memiliki program yang dapat mencegah obesitas pada anak secara signifikan dimana ditemukan nilai p